The Effect of Different Doses of Probiotics Minaraya in the Feed on the Growth and Survival Rate of Green Catfish (Hemibagrus Nemurus) With Recirculation System - Mukromin Mukromin; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This study aims to determine the effect of different doses of probiotics minaraya in feed on the growth and survival of baung fish (Hemibagrus nemurus) maintained with resirculation system. This research was conducted from March - April 2021 at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The container used was an aquarium measuring 60 cm x 40 cm x 40 cm as many as 15 units with a stocking density of 15 fish/60 L. This study used a completely randomized design method (CRD) one factor with five levels of treatment and three repetitions. The level of treatment applied in the study was P0 = without giving probiotik minaraya (Control), P1 = dose of probiotik minaraya 2 mL/kg of feed, P2 = dose of probiotik minaraya 4 mL/kg of feed, P3 = dose of probiotik minaraya 6 mL/kg of feed and P4 = dose of probiotik minaraya 8 mL/kg of feed. The results showed that giving probiotik minaraya with different doses in the feed had a significant effect (P<0.05) on growth but had no significant effect (P>0.05) on the survival rate of the baung fish seeds. The best treatment was found at a probiotik minaraya dose of 8 mL/kg of feed, which produced feed digestibility rate (59,3 %), protein digestibility rate (85,3 %), total weight growth (7,86±0,07 g), total length growth (7,17±0,37 cm), specific growth rate (3,20±0,20 %), feed efficiency (68,92±0,72 %), feed conversion (1,46±0,05 %), survival rate (93,33±2,89 %). Water quality parameter recorded were : temperature 27,7-28,5 ºC, power of hydrogen 6,22-7,12, dissolved oxygen (DO) 3,07-7,07 mg/L , and ammonia (NH3) 0,00016- 0,00501 mg/L.